2022
DOI: 10.21203/rs.3.rs-1451730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing analysis to evaluate the influence of T2DM on polymorphisms associated with drug resistance in M. tuberculosis

Abstract: BackgroundType 2 diabetes mellitus (T2DM) has been associated with treatment failure, and the development of drug resistance in tuberculosis (TB). Also, whole-genome sequencing has provided a better understanding and allowed the growth of knowledge about polymorphisms in genes associated with drug resistance. Considering the above, this study analyzes genome sequences to evaluate the influence of type 2 diabetes mellitus in the development of mutations related to tuberculosis drug resistance. M. tuberculosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been reported that rifampicin-resistant M. tuberculosis strains isolated from HIV-coinfected patients carry more resistance-conferring mutations in rpoB and are associated with low fitness in the absence of the drug [28]. It has recently been described that some specific variations are associated with T2DM in DNA reparation genes in M. tuberculosis [29]; however, no differences have been described in the polymorphisms observed in canonical genes related to antibiotic resistance in individuals with the binomial TB-T2DM [30], suggesting that the high frequency of resistance observed in individuals with T2DM may be due to the rapid and early occurrence of variants in the resistance genes that allow rapid development [31]. The present study therefore aimed to evaluate the influence of T2DM in the dynamics of polymorphism generation related to the development of antibiotic resistance in M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rifampicin-resistant M. tuberculosis strains isolated from HIV-coinfected patients carry more resistance-conferring mutations in rpoB and are associated with low fitness in the absence of the drug [28]. It has recently been described that some specific variations are associated with T2DM in DNA reparation genes in M. tuberculosis [29]; however, no differences have been described in the polymorphisms observed in canonical genes related to antibiotic resistance in individuals with the binomial TB-T2DM [30], suggesting that the high frequency of resistance observed in individuals with T2DM may be due to the rapid and early occurrence of variants in the resistance genes that allow rapid development [31]. The present study therefore aimed to evaluate the influence of T2DM in the dynamics of polymorphism generation related to the development of antibiotic resistance in M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%